Pengembangan Website Sistem Persuratan Online Desa Tamban Menggunakan Framework Laravel dengan Metode Extreme Programming (XP) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study focuses on the development of an online correspondence system website in Tamban Village with the aim of facilitating more effective and efficient access to and management of administrative correspondence services for the community, village officials, and administrators. The Extreme Programming (XP) method was used, which includes the phases of planning, design, coding, and testing. To ensure that the system met user requirements, data were collected through observation, interviews, and literature review, and then analyzed using qualitative and quantitative descriptive analysis techniques to evaluate system requirements and the results of system testing. The findings show that, through an iterative development approach involving system analysis, construction, and testing, the developed website was able to improve the effectiveness and efficiency of correspondence services. As a result, this online correspondence system can meet user needs, provide practical solutions for managing village administration, and help improve the quality of public services by making them more efficient, transparent, and structured. This study is limited by the fact that system testing was conducted on a limited scale and did not include in-depth cybersecurity testing, therefore, future research is recommended to develop more comprehensive security features and conduct system testing with a larger number of users.